INFLUENCE HYDROGEN INTERCALATION ON THE ELECTROCHEMICAL PROPERTIES InSe - Kvashnivska, N. M. (Computer Science and Applied Mathematics, 2016)
The study of layered crystals associated with the possibility of implementation in these compounds physical phenomena at nanoscale level, and their practical use. The investigation of physical and electrochemical laws of the quantum formation of structures of a laminates caused by the lackof data about the peculiarities of the nucleation of nanoclusters by forming the respective ther modynamic conditions or by cooperation with an external factors and on the cleavage surfaceand in arrays of the bulk solid materials. Specifically the introduction of the hydrogen changes layered crystal properties that are sensitive to the intercalants. Some scientific interest has a comparison of the electrochemical properties of purecrystal InSe and InSe that intercalated by hydrogen. Experimentally that hydrogen doping to the lamellar crystal InSe improves the anodic and cathodic reactions in acid (H2SeO3, H2SO4) and neutral (water) mediums. The H2SeO3 medium solution give us the less negative quantity of the electrode potential for the pure crystal in illumination and in the dark among the medium of the distilled water. There are intensive processes of polarization in the normal H2SO4 even without the solar radiation and we can observe it in hydrogenated and in pure crystal as well. Taking into consideration the results that we get in acid (sulfuric acid) and in the neutral mediums we establish that anodic and cathodic reactions are slower in the negative potential values compared to the medium o selenic acid. Anodic and cathode processes in the dark (without sunlight) are at a lower rate than under sunlight. This is caused by strengthening of anodic and cathode reactions, and the anode reaction proceeds intensively.Intercalationshifts the equilibriumelectrode potential towards to the guest element potential and dark photoanodic potential shifts to the cathode side depending on the degree of intercalation, but sensitivity of photoanode at the same time becomes worse. The lighting amplify the loss of an electron from an electrode as well as selective dissolution of the semiconductor elements, promoting them to transition to the ionic condition. The environments in the form of crust and drops that are formed on the surface affected on the surface characteristics of the studied semiconductor.